Rectopexy for Rectal Prolapse - Alam, Nasra N.; Narang, Sunil K.; Köckerling, Ferdinand; Daniels, Ian R.; Smart, Neil J. (Frontiers in Surgery, 2015)
Introduction Ventral mesh rectopexy (VMR) is a recognised treatment for posterior compartment pelvic organ prolapse (POP). The aim of this review is to provide a synopsis of the evidence for biologic mesh use in VMR, the most widely recognised surgical technique for posterior compartment POP. Methods A systematic search of PubMed was conducted using the search terms ‘VMR’, ‘ventral mesh rectopexy’ or ‘mesh rectopexy’. Six studies were identified. Results 268/324 patients underwent ventral rectopexy using biological mesh with a further 6 patients having a combination of synthetic and biological mesh. Recurrence was reported in 20 patients; however, 6 were from studies where data on biological mesh could not be extracted. There are no RCTs in VMR surgery and no studies have directly compared types of biologic mesh. Cross-linked porcine dermal collagen is the most commonly used mesh and has not been associated with mesh erosion, infection or fistulation in this review. The level of evidence available on the use of biologic mesh in VMR is of low quality (level 4). Conclusions VMR has become prevalent for posterior compartment POP. The evidence base for its implementation is not strong and the quality of evidence to inform choice of mesh is poor.